Manpower Obsolescence: A New Definition and Empirical Investigation of Personal Variables - Shearer, Richard L.; Steger, Joseph A. (Academy of Management Journal, 1975)
Of twelve major determinants of managerial and technical job obsolescence, high need achievement and high levels of organizational participation were found to be the major contributors to nonobsolescence. Managerial obsolescence, as opposed to professional obsolescence, tended to depend more on experience and less on education.